Analisis Kemampulabaan Perusahaan Sektor Barang Konsumsi - Marcellia Susan; Jacinta Winarto (Jurnal Informatika Ekonomi Bisnis, 2024)
This research analyzes the profitability of companies in the consumer goods sector. This research aims to examine the relationship between debt and equity ratios, company size, interest rates, and company profitability. This research uses a sample of consumer goods sector companies listed on the Indonesia Stock Exchange. Secondary data relevant to the research variables was obtained from financial reports and processed using multiple regression techniques. The findings of this research indicate the contribution of indicators measuring capital structure, company size, and interest rates in determining a company's profitability. Besides, the research results also show that interest rates moderate the relationship between the debt and equity ratio and the profitability of companies in the consumer goods sector.